ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI PENGUSAHA UMKM TERHADAP LAPORAN KEUANGAN BERBASIS SAK EMKM - Silvia, Bella; Azmi, Fika (Jurnal Analisis Bisnis Ekonomi, 2019)
This study aims to analyze the factors that influence the perception of MSME entrepreneurs regarding the importance of SAK EMKM-based financial statements. These factors include the level of education, utilization of information technology, length of business, turnover and provision of information and socialization of SAK EMKM. The data used in this study was obtained from a questionnaire. The population in this study was furniture SMEs in Jepara Regency. Determination of the sample used quota sampling so that 75 furniture SMEs were selected in Jepara Regency. The data analysis tool used is multiple linear regression analysis. The results showed that the level of education, utilization of information technology and length of business did not affect the perception of MSME entrepreneurs regarding the importance of SAK EMKM-based financial statements. However, the turnover and the provision of information and socialization of SAK EMKM had a positive effect on the perception of MSME entrepreneurs regarding the importance of EMKM-based SAK financial statements in furniture SMEs in Jepara District.